2019
DOI: 10.1038/s41598-019-41380-1
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine effectively enhances antitumor activity of temozolomide in vitro and in vivo mediated by increased autophagy and Caspase-3 dependent apoptosis

Abstract: Gliomas are incurable solid tumors with extremely high relapse rate and definite mortality. As gliomas readily acquire resistance to only approved drug, temozolomide (TMZ), there is increasing need to overcome drug resistance by novel therapeutics or by repurposing the existing therapy. In the current study, we investigated antitumor efficacy of roscovitine, a Cdk inhibitor, in combination with TMZ in vitro (U87, U373, LN 18 and C6 cell lines) and in vivo (orthotopic glioma model in Wistar rats) glioma models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Resistance to TRAIL-mediated apoptosis in GBM was overcome by roscovitine's ability to downregulate survivin, XIAP and Mcl-1 [97,98] . More recently, using glioma cell lines and an in vivo orthotopic glioma model, the combination of roscovitine with TMZ was shown to result in increased autophagy and caspase-3 mediated cell death [99] . Menn et al [100] showed the ability of roscovitine to cross the BBB in healthy adult rats while studying ischemic stroke.…”
Section: Ckis In Glioma Treatment -Preclinical Studiesmentioning
confidence: 99%
“…Resistance to TRAIL-mediated apoptosis in GBM was overcome by roscovitine's ability to downregulate survivin, XIAP and Mcl-1 [97,98] . More recently, using glioma cell lines and an in vivo orthotopic glioma model, the combination of roscovitine with TMZ was shown to result in increased autophagy and caspase-3 mediated cell death [99] . Menn et al [100] showed the ability of roscovitine to cross the BBB in healthy adult rats while studying ischemic stroke.…”
Section: Ckis In Glioma Treatment -Preclinical Studiesmentioning
confidence: 99%
“…Inhibiting Cdk5 in glioma cells (either in vivo or in vitro) increases the rate of autophagy and of caspase-3-dependent apoptosis. Co-treatment with RSV plus TMZ prevented the glioma growth, reduced angiogenesis, and limited tumor dissemination by reducing the number of reactive astrocytes [209].…”
Section: The Standard Care: Temozolomidementioning
confidence: 94%
“…Inhibition of Cdk5 increase autophagy and apoptosis dependent of caspase-3; decreases the levels of Ki67, GFAP, VEGF, and CD31; reduces tumor progression by decreasing reactive astrocytes surrounding the glioma [209].…”
Section: Roscovitine (Cyclin-dependent Kinase Cdk Inhibitor)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclin-dependent kinase-5(Cdk-5), a threonine or serine kinaseis overexpressed in glioma cells in comparison to the healthy human astrocytes is responsible for neuronal dysfunction and death [198]. Pandey (2019) reported both in vitro and in vivo enhancement of the antitumour activity of temozolomide (TMZ) by the drug Roscovitine (RSV) known to inhibit Cdk-5 [199,200]. This is an interesting result since use of TMZ alone is not effective for gliomas after a while due to the development of drug resistance by malignant cells.…”
Section: Drug Repurposing For Cancermentioning
confidence: 99%